A STABILITY, ACCURACY, AND ROBUSTNESS REPRESENTING LIQUID CHROMATOGRAPHIC METHOD FOR THE QUANTIFICATION OF ZANUBRUTINIB AND ITS SPECIFIED IMPURITIES - KANTHETI, SUBHASHINI; RAJU, R. RAMESH (International Journal of Applied Pharmaceutics, 2023)
Objective: An innovative RP-HPLC isocratic method was established and then validated using Zanubrutinib and its specified impurities (Impurity-1, Impurity-2, Impurity-3, Impurity-4, and Impurity-5). Methods: In this method, effective chromatographic separation was given an X-Bridge Phenyl column measuring 250 mm x 4.6 mm, packed column with 5μ as a particle size. Acetonitrile, 1% Ortho Phosphoric acid (pH: 2.7), and methanol in the volume ratios 40, 40, and 20 were utilized as a mobile phase at room temperature with an optimized 1.0 ml/min flow rate. Wavelength was detected at 225 nm by using a PDA detector. Results: Retention times of zanubrutinib and its specified impurities were recorded at 13.284, 4.730, 6.816, 9.583, 10.726, and 12.287. Moreover, other parameters USP tailing is good, USP plate count above 4000, and USP resolution is greater than are equal to 2. The Obtained peaks are homogeneous, hence the purity angle is less than the purity threshold and No Purity Flag. According to ICH guidelines, this method was validated. Zanubrutinib (5-75 µg/ml), their quantified impurity-1, impurity-2, impurity-4, impurity-5 (0.1-1.5 µg/ml), and impurity-3 (0.1-1.5 µg/ml) are proved through linearity method in between LOQ to 75 quantified levels. The % recovery was present between 100.18-95.85, 103.15-93.80, which is a good and acceptance range (amongst 85% and 115%) for drug and specified impurities. The limit of quantitation (LOQ) and limit of detection (LOD) values were assessed for zanubrutinib and its specified impurities were tabulated. These values were calculated using slope (σ) and standard deviation (SD) methods. Method precision (M. P.) and Intermediate (I. P.) Intermediate (I. P.) precision was estimated by evaluating several (six) samples of a similar batch as per the planned technique on the day and the next day, using different columns and systems. Robustness information significantly affects the resolution between Zanubrutinib and specified impurities. The remaining parameters do not impact the parameter’s system suitability. Conclusion: Hence this method was chosen for common analysis. Finally, the system-suitable parameters and validation parameters values are acceptable limits.